Chimeric antigen receptor T cells targeting the GM3(Neu5Gc) ganglioside - Heinzelbecker, Julia; Fauskanger, Marte; Jonson, Ida; Krengel, Ute; Løset, Geir Åge; Munthe, Ludvig; Tveita, Anders (Frontiers in Immunology, 2024)
Chimeric antigen receptor (CAR) T cell technology has ushered in a new era of immunotherapy, enabling the targeting of a broad range of surface antigens, surpassing the limitations of traditional T cell epitopes. Despite the wide range of non-protein tumor-associated antigens, the advancement in crafting CAR T cells for these targets has been limited. Owing to an evolutionary defect in the CMP-Neu5Ac hydroxylase (CMAH) that abolishes the synthesis of CMP-Neu5Gc from CMP-Neu5Ac, Neu5Gc is generally absent in human tissues. Despite this, Neu5Gc-containing antigens, including the ganglioside GM3(Neu5Gc) have consistently been observed on tumor cells across a variety of human malignancies. This restricted expression makes GM3(Neu5Gc) an appealing and highly specific target for immunotherapy. In this study, we designed and evaluated 14F7-28z CAR T cells, with a targeting unit derived from the GM3(Neu5Gc)-specific murine antibody 14F7. These cells exhibited exceptional specificity, proficiently targeting GM3(Neu5Gc)-expressing murine tumor cells in syngeneic mouse models, ranging from B cell malignancies to epithelial tumors, without compromising safety. Notably, human tumor cells enhanced with murine Cmah were effectively targeted and eliminated by the 14F7 CAR T cells. Nonetheless, despite the detectable presence of GM3(Neu5Gc) in unmodified human tumor xenografts, the levels were insufficient to trigger a tumoricidal T-cell response with the current CAR T cell configuration. Overall, our findings highlight the potential of targeting the GM3(Neu5Gc) ganglioside using CAR T cells across a variety of cancers and set the stage for the optimization of 14F7-based therapies in anticipation of future human clinical applications.